2014
DOI: 10.1210/jc.2014-1734
|View full text |Cite
|
Sign up to set email alerts
|

Novel Genome-Wide Association Study–Based Candidate Loci for Differentiated Thyroid Cancer Risk

Abstract: Our findings provide evidence for novel DTC susceptibility variants. Further studies are warranted to identify the specific genetic variants responsible for the observed associations and to functionally validate our in silico predictions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
47
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 32 publications
8
47
1
Order By: Relevance
“…Similarly, no association signal was observed in the genomewide step of this study for other markers identified previously (rs966423 at 2q35 and rs2439302 at 8p12 17 or rs10136427 at 14q24.3 and rs7267944 at 20q12 29 ). As all of these genetic variants were described in a single study, without replication by subsequent studies, they could be associated with the disease in a population-specific manner.…”
Section: Discussioncontrasting
confidence: 46%
“…Similarly, no association signal was observed in the genomewide step of this study for other markers identified previously (rs966423 at 2q35 and rs2439302 at 8p12 17 or rs10136427 at 14q24.3 and rs7267944 at 20q12 29 ). As all of these genetic variants were described in a single study, without replication by subsequent studies, they could be associated with the disease in a population-specific manner.…”
Section: Discussioncontrasting
confidence: 46%
“…This limitation is solved by genome-wide association studies (GWASs) in which the whole genome is analyzed without formulating any a priori hypothesis. GWASs on DTC allowed discovering novel variants, including those near FOXE1, DIRC3, NKX2-1 (15)(16)(17) and, more recently, those near IMMP2L, RARRES1, SNAPC4/CARD9, ARSB, BATF, DHX35, SPATA13, GALNTL4, and FOXA2 (18)(19)(20). However, to ensure a high quality and to prevent false-positive findings, highly stringent criteria are applied in the GWASs with the disadvantage of excluding SNPs truly associated with the risk.…”
Section: Introductionmentioning
confidence: 99%
“…The advent of genome-wide association studies (GWAS) constituted a breakthrough in the ability to study the genetics of complex diseases. Single nucleotide polymorphisms (SNPs) associated with a low to medium risk for PTC have been described in several GWAS studies (5)(6)(7)(8)(9). The first variants uncovered by GWAS were rs965513 (9q22), rs944289 (14q13), rs116909374 (14q13), rs2439302 (8p12), and rs966423 (2q35) (5,6).…”
mentioning
confidence: 99%